Does neoadjuvant/perioperative chemotherapy improve overall survival for T2N0 gastric adenocarcinoma?. Issue 4 (11th November 2017) - Gabriel, Emmanuel; Attwood, Kristopher; Narayanan, Sumana; Brady, Maureen; Nurkin, Steven; Hochwald, Steven; Kukar, Moshim
Abstract : Background: The purpose of this study was to determine whether neoadjuvant and/or perioperative chemotherapy (NAC) has an overall survival (OS) benefit for patients with T2N0 gastric adenocarcinoma. Study Design: We performed retrospective analyses using the National Cancer Data Base, 2004‐2013. Patients with T2N0 gastric adenocarcinoma were divided into two treatment groups: (1) NAC plus surgery (NA + S) and (2) surgery alone (S). Results: Of 1, 704 patients included, 277 (16.3%) received NAC, and 1, 427 (83.7%) were treated with surgery alone. Patients in the NA + S group were more likely to be younger, have fewer comorbidities, and have larger tumors located in the proximal stomach. Although in an unadjusted analysis of OS, the NA + S group had improved survival compared to the S group (HR = 0.81, 95% CI 0.67‐0.99, P < 0.0001), this was not maintained in a propensity adjusted analysis (HR = 0.89, 95% CI 0.68‐1.18, P = 0.42). Similarly, propensity adjusted analyses accounting for potential bias from clinical misstaging or treatment effect from NAC did not show any OS benefit from NAC. Conclusion: Based on the largest cohort of clinically staged T2N0 gastric adenocarcinoma, there was no OS benefit derived from NAC compared to surgery alone. For select patients with reliable preoperative staging, NAC may be omitted.